Kinerja Penyuluh Pertanian di BPP Toware Kabupaten Jayapura - Alum, Turnip; Lefaan, Avelinus; Sitorus, Ferry R. P. P. (JURNAL EKOLOGI BIROKRASI, 2024)
This study aims to evaluate the performance of agricultural extension workers in BPP Toware, Jayapura Regency, and the factors influencing their effectiveness. The research used a descriptive qualitative method, with in-depth interviews, direct observation, and documentation as the main research instruments. Data were collected through purposive sampling, involving agricultural extension workers and farmers as key informants. The data analysis employed thematic analysis, including data reduction, presentation, and conclusion drawing. The findings revealed that although extension workers play a critical role in farmer empowerment, their performance is hindered by several challenges, such as insufficient facilities, low welfare levels, and inadequate training. Another significant factor affecting performance is the varied educational background, with a dominance of high school graduates among contract workers, limiting their technical competency. Consequently, the performance of extension workers in fostering behavioral change towards sustainable agricultural development remains suboptimal.